Transnational News Audiences and the Limits of Cultural Decolonisation in Zambia: Media Coverage of the Soweto Uprising of 1976. Issue 4 (4th July 2021) - Brooke, Peter
Abstract : This article takes news coverage of the Soweto uprising of 1976 as a case study to demonstrate the influence of South Africa and Britain on the media in post-colonial Zambia. In part, this can be accounted for by the growing popularity of Radio Republic of South Africa (RSA) among listeners in Zambia, particularly in regions that were on the front line of the liberation struggle. RSA defended the actions of the South African police, as did the BBC World Service. Remarkably, Zambia's own press and broadcast services also took a similar line at times, thanks to their reliance on Reuters news agency, which, in turn, made uncritical use of South African government sources. However, by reading news content in the light of audience research data, it is argued that, in other ways, Zambian independence represented a meaningful departure from the colonial past. Decolonisation enabled the development of a more pluralistic culture of news consumption, a trend further encouraged by an international boom in transistor-radio sales with short-wave capability. Zambia's news culture also illustrated the limits of one-party rule. Although Kenneth Kaunda sought to emulate the stifled atmosphere of the Northern Rhodesian media, it proved impossible in the changed circumstances of the later 1960s and 1970s.